Cardiac markers in left-sided breast cancer patients receiving adjuvant radiotherapy: a prospective study - Kundan Chufal; Irfan Ahmad; Anuj Prakash; Alexis Miller; Preetha Umesh; Varsha Koul; Ram Bajpai; Bharat Dua; Priya Gupta; Munish Gairola (Cardio-Oncology, 2024)
Abstract Objectives To investigate the association between radiotherapy (RT) and cardiac biomarkers in women with left-sided breast cancer. Methods This prospective observational study recruited patients with stage I-III left-sided breast cancer without coronary heart disease who required adjuvant RT. High-sensitivity troponin I(hsTnI), N-terminal pro-brain natriuretic peptide(NT-proBNP), and high-sensitivity C-reactive protein(hsCRP) levels were measured pre-RT, immediately after RT, and 3 months post-RT. Cardiac-sparing RT techniques were utilized (Field-in-Field IMRT/VMAT ± voluntary deep inspiration breath-hold). Statistical analyses were performed using non-parametric tests and multivariable quantile regression (QR). Results One hundred five patients completed the study, with 63 evaluable at three months post-RT. Pre- and post-RT biomarkers showed no significant differences. Median pre-RT and post-RT values were: hsTnI (0.012ng/mL; 0.012ng/mL), hsCRP (3.1 mg/L; 2.8 mg/L), and NT-proBNP (59pg/mL; 45pg/mL). Three months post-RT, hsTnI, hsCRP and NT-proBNP levels also showed no significant differences. Multivariable QR revealed no association between heart Dmean [median(IQR): 2.87 Gy (2.05–3.94)] and post-RT biomarkers. Age and BMI were associated with hsCRP and NT-proBNP, respectively. Conclusions hsTnI, NT-proBNP, and hsCRP are not correlated with contemporary low cardiac exposure in left-sided breast cancer patients treated with contemporary RT techniques.